2002
DOI: 10.1093/jac/49.1.161
|View full text |Cite
|
Sign up to set email alerts
|

The fate of antibiotic resistance marker genes in transgenic plant feed material fed to chickens

Abstract: We have examined the fate of an antibiotic resistance marker, incorporated into transgenic maize when fed to chicks. Plant-derived markers were found in the crops of five birds fed transgenic maize and in the stomach contents of two birds. The plant-derived marker gene was not found in the intestines. The survival of the antibiotic resistance marker gene mirrored that of plant DNA targets, demonstrating that it survives no better than other DNA and indicating that it is very unlikely that bacteria in the gut o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 7 publications
1
27
2
1
Order By: Relevance
“…The high level of degradation of ubiquitous plant chloroplast DNA in the last section of cattle GIT (jejunum and colon) has been demonstrated by Einspanier et al (2004). In the GIT of monogastrics, plant DNA is detectable in pigs (Klotz et al, 2002;Chowdury et al, 2003;Reuter and Aulrich, 2003), in chickens (Chambers et al, 2002) and in humans (Martìn-Orù e et al, 2002;Netherwood et al, 2004).…”
Section: Dnamentioning
confidence: 98%
“…The high level of degradation of ubiquitous plant chloroplast DNA in the last section of cattle GIT (jejunum and colon) has been demonstrated by Einspanier et al (2004). In the GIT of monogastrics, plant DNA is detectable in pigs (Klotz et al, 2002;Chowdury et al, 2003;Reuter and Aulrich, 2003), in chickens (Chambers et al, 2002) and in humans (Martìn-Orù e et al, 2002;Netherwood et al, 2004).…”
Section: Dnamentioning
confidence: 98%
“…Deaville and Maddison (2005) reported that transgenic DNA from RR soybean meal or Bt maize was detectable in the broiler gizzard, but not in intestinal digesta. An experiment with broilers has shown that the bla gene (part of the Bt construct from Bt176 GM maize) was present in the gizzard content, but not in small intestine, caecum and rectum digesta (Chambers et al 2002). Such a high degradation and digestion of plant DNA in the alimentary tract of animals makes the possibility of GM DNA transfer to gut bacterial very improbable.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro forced filter mating study, Netherwood et al (1999) found that gene transfer occurred at a rate of less than 10 -8 . In order for horizontal transfer to occur, DNA must first be released from the donor organism in a form which can be incorporated into the genome of a putative recipient bacterium and must remain intact for a sufficient time for the transfer to occur (Chambers et al, 2002).…”
Section: Discussionmentioning
confidence: 99%